Corosolic Acid Inhibits Secretory Phospholipase A2IIa as an Anti-Inflammatory Function and Exhibits Anti-Tumor Activity in Ehrlich Ascites Carcinoma Bearing Mice - Pundalik S; Hanumappa KR; Giresha AS; Urs D; Rajashekarappa S; Muniyappa N; Jamballi G M; Kuaramkote Shivanna D; S Meti R; Anekere Dasappa Setty S; Thippegowda PB; Krishnappa DK (Journal of Inflammation Research, 2022)
Sophiya Pundalik,1 Krishna Ram Hanumappa,2 Aladahalli S Giresha,3 Deepadarshan Urs,1 Sharath Rajashekarappa,4 Narayanappa Muniyappa,1 Manjunatha Jamballi G,5 Devaraju Kuaramkote Shivanna,6 Rajkumar S Meti,1 Sathisha Anekere Dasappa Setty,7 Prabhakar Bettadathunga Thippegowda,8 Dharmappa Kattepura Krishnappa1 1Inflammation Research Laboratory, Department of Studies and Research in Biochemistry, Mangalore University, Jnana Kaveri Post Graduate Campus, Kodagu, Karnataka, India; 2Nisarga Research and Development Trust (T), Bengaluru, Karnataka, India; 3Department of Biochemistry, School of Science, Jain (Deemed-to-be University), Bangalore, Karnataka, India; 4Department of Food Technology, Davanagere University, Davanagere, Karnataka, India; 5Department of Chemistry FMKMC College Madikeri, Mangalore University Constituent College, Mangalore, Karnataka, India; 6Department of Biochemistry, Karnataka University, Dharwad, Karnataka, India; 7Division of Biochemistry, School of Life Sciences, JSS Academy of Higher Education & Research, SS Nagar, Mysore, Karnataka, India; 8Molecular Biomedicine Laboratory, Postgraduate Department of Studies and Research in Biotechnology, Sahyadri Science College (Autonomous), Kuvempu University, Shivamogga, Karnataka, IndiaCorrespondence: Dharmappa Kattepura Krishnappa, Email dharmappa@gmail.comBackground: Inflammation is generally connected to tumour progression and development. The secretory phospholipase A2IIa (sPLA2IIa) is an important inflammatory enzyme that catalyse the hydrolysis of membrane phospholipids into arachidonic and lysophosphatidic acid, which are the precursors for production of a lot of pro-inflammatory mediators like prostaglandins, prostacyclins, thromboxanes, leukotrienes and platelet activating factors, which involved in the proliferation, migration, invasion, and metastasis. Therefore, investigating safe and effective sPLA2IIa inhibitors as a therapeutic agent to treat cancer is indeed in need.Methods: Anti-inflammatory function of corosolic acid was evaluated by docking it with sPLA2IIa enzyme, sPLA2IIa inhibition, calcium and substrate concentration-dependent assays; intrinsic fluorescence and UV-CD analysis; neutralisation of sPLA2IIa induced indirect hemolytic and edema. Evaluated the anticancer activity of corosolic acid by MTT assays and caspase-3 expression; the anti-tumour activity by EAC-induced cell line and interleukin 6 expression.Results: The corosolic acid inhibits sPLA2IIa activity to 82.21± 2.82%. The inhibition was evaluated by increasing calcium from 2.5 to 15 μM and substrate from 20 to 120 nM, it did not affect the level of inhibition. Corosolic acid altered the intrinsic fluorescence and UV-CD spectra of sPLA2IIa enzyme, indicating the direct interaction. It neutralised sPLA2IIa induced hemolytic activity from 97± 1.23% to 15.75± 1.44% and edema from 171.51± 2.39% to 119.3± 2.6%. Further, as antiproliferative activity, corosolic acid reduced the PC3 cell viability from 99.66± 0.57% to 23± 2.64% and suppressed LPS-induced IL-6 level from 94.35± 2.2% to 34.36± 2.4%. It increased mean survivability time from 30 to 38 days and displayed the drug-like qualities.Conclusion: All the experimental results have proven the corosolic acid as an anti-inflammatory and anticancer molecule that may further be used to develop it as a drug.Keywords: corosolic acid, antioxidant, secretory phospholipase A2 IIa inhibition, caspase 3, IL-6, prostate cancer, EAC, ADME-toxicity, Anti-inflammatory